PROBES: Early-stage explorations of digital potential across CGIAR - Alliance of Bioversity International and CIAT; International Water Management Institute - IWMI (2025)
This brief presents PROBES, a CGIAR-wide approach led by the Digital Transformation Accelerator to test emerging digital technologies in real-world contexts before they are scaled. It outlines how probes enable researchers to explore new tools safely, generate actionable learning including from failures, and guide smarter investment decisions aligned with CGIAR’s 2030 outcomes. Drawing on more than 25 active probes, the brief demonstrates how early experimentation helps CGIAR focus on digital innovations with real transformative potential.